An Investigation of the Student Learning Satisfaction Model for User Story Learning in Software Engineering Course - Zul, Muhammad Ihsan; Mohd. Yasin, Suhaila; Sahid, Dadang Syarif Sihabudin (Society of Visual Informatics, 2024)
Software engineering courses are essential for students to become professional software engineers. These courses expose them to their first user stories (US). Despite extensive studies on US-related issues, quality remains the most prominently discussed topic. Therefore, it is essential to investigate US education in higher education to produce qualified software practitioners. In the educational context, such investigations are typically measured using the learning satisfaction approach. This study aims to investigate the suitability of the learning satisfaction model in software engineering courses, specifically in the US context. Subsequently, the study will identify opportunities for improving US teaching methods. The applied learning satisfaction model consists of four factors: perceived ease of use, perceived usefulness, learning motivation, and learning satisfaction. These factors are derived by combining the Technology Acceptance Model (TAM) and Learning Motivation Theory. The study employs Confirmatory Factor Analysis (CFA) using the partial least squares structural equation modelling (PLS-SEM). The measurement model and model evaluation fit stages are used to assess the suitability of the implemented learning satisfaction model. The structural model examines opportunities for improving the US teaching method based on the identified factors. The study involves 142 software engineering students as respondents. The results indicate that the current model requires adjustments in indicators and model fit, particularly SRMR and NFI, to align with the study. Regarding learning enhancement, the factors of perceived ease of use and perceived usefulness suggest that improvements in US teaching methods are necessary to increase student learning satisfaction in US learning.